Perceptions and Practice of Preconception Care by Healthcare Workers and High-Risk Women in South Africa: A Qualitative Study - Winifred Chinyere Ukoha (MDPI AG, 2021)
Preconception care is biomedical, behavioural, and social health interventions provided to women and couples before conception. This service is sometimes prioritised for women at high risk for adverse pregnancy outcomes. Evidence revealed that only very few women in Africa with severe chronic conditions receive or seek preconception care advice and assessment for future pregnancy. Thus, this study aimed to explore the perceptions and practice of preconception care by healthcare workers and high-risk women in Kwa-Zulu-Natal, South Africa. This exploratory, descriptive qualitative study utilised individual in-depth interviews to collect data from 24 women at high risk of adverse pregnancy outcomes and five healthcare workers. Thematic analysis was conducted using Nvivo version 12. Five main themes that emerged from the study include participants’ views, patients’ access to information, practices, and perceived benefits of preconception care. The healthcare workers were well acquainted with the preconception care concept, but the women had inconsistent acquaintance. Both groups acknowledge the role preconception care can play in the reduction of maternal and child mortality. A recommendation is made for the healthcare workers to use the ‘One key’ reproductive life plan question as an entry point for the provision of preconception care.